Frank Netter: A Man of Art and Science. Issue 5 (May 2016) - Shivakumar, Natesh; Hammad, Abdulrahman Y.; Gamblin, T. Clark
Medical illustrations are highly used by medical professionals for various reasons. They have facilitated learning for many centuries and allowed a detailed analysis of subjects. Complex information on anatomy, histology, physiology, and even surgical procedures can be transformed by illustrations into a clear and accurate source that words could never fully describe. The idea that art can be used to enhance the study of science has been emphasized by many medical illustrators. One person who will always be remembered for his artwork in the modern era is Frank H. Netter. The New York native, born in 1906, is one of the era's most well-known medical illustrators. Almost all medical professionals, at one point or another, have come across one of his numerous artistic sketches during their career. Although best known for his Atlas of Human Anatomy, some of Netter's other projects include the CIBA Collection of Medical Illustrations, the "Transparent Women, " and the Clinical Symposia series. Medicine lost an educator and an artist in 1991; however, his collection of illustrations remains as his lasting gift to the field.